Relationship Between Entrepreneur's Value,Firm Financing, Firm Management, Market Practices, and Growth Performance of Small-Medium Enterprises in Cambodia - Peou, Chea (2009)
The aims of this study are to examine the relationship between entrepreneur’s value,firm financing, firm management, market practices, and growth performance of Small-Medium Enterprises (SMEs) in Cambodia. This study also examined the moderating influence of government policy on the relationship between entrepreneur’s value, firm financing, firm management, market practices, and growth performance of SMEs. In determining this relationship, a hypothetical model were developed testing the relationship between entrepreneur’s value, firm financing, firm management, and market practices as independent variables; and government policy as moderating variable; and the growth performance of SMEs as dependent variable. The questionnaires were distributed and 220 questionnaires were usable for data analysis. The quantitative data were processed using a SPSS version 15.0 program. Descriptive statistics used to describe the respondents’ profile and variable items. Correlation,linear, multiple and hierarchical regressions used for inferential statistics. The result on the empirical relationship between entrepreneur’s value, firm financing, firm management, market practices, and moderated by government policy were contributed positively to the growth performance of SMEs as hypothesized. The positive association between the combinations among all independent variables to dependent variable was supported. The results also suggested that government policy had positive and significant moderating influence on the model.